Unrelated donor transplantation with posttransplant cyclophosphamide vs ATG for myelodysplastic neoplasms - Chalandon, Yves; Eikema, Diderik-Jan; Moiseev, Ivan; Ciceri, Fabio; Koster, Linda; Vydra, Jan; Passweg, Jakob; Rovira, Montserrat; Ozcelik, Tulay; Gedde-Dahl, Tobias; Kröger, Nicolaus; Potter, Victoria; et al. (Blood advances, 2024)
It has been reported in prospective randomized trials that antithymocyte globulin (ATG)-based graft-versus-host disease (GVHD) prophylaxis has benefits in the setting of allogeneic hematopoietic stem cell transplantation (allo-HSCT) with unrelated donors (UDs). However, the optimal GVHD prophylaxis strategy has been challenged recently by the increasing use of posttransplant cyclophosphamide (PTCY). We report from the European Society for Blood and Marrow Transplantation registry the outcomes of 960 patients with myelodysplastic neoplasms who underwent allo-HSCT from UD with PTCY or ATG as GVHD prophylaxis. The primary outcomes were overall survival (OS) and progression-free survival (PFS). The disease characteristics were similar in both groups. Day 28 neutrophil engraftment was significantly better with ATG (93% vs 85%). Over a median follow-up of 4.4 years, the 5-year OS was 58% with PTCY, and 49% in the ATG group. The 5-year PFS was higher for PTCY at 53% vs 44% for ATG. Grade 2 to 4 acute GVHD incidence was lower when PTCY was used (23%), whereas there was no difference in the incidence of chronic GVHD at 5 years. Multivariable analyses confirmed better OS and PFS with PTCY with a hazard ratio (HR) for ATG of 1.32 (1-1.74) and a better PFS for PTCY with a HR for ATG of 1.33. This study suggests that GVHD prophylaxis using PTCY instead of ATG in this setting remains a valid option. Further prospective randomized studies would be essential to confirm these results.
Keywords: výsledek terapie; Young Adult; Male; mladý dospělý; Cyclophosphamide; Myelodysplastic Syndromes; Transplantation, Homologous; Adolescent; nemoc štěpu proti hostiteli; Adult; transplantace hematopoetických kmenových buněk; Aged; dospělí; mužské pohlaví; senioři; příprava pacienta k transplantaci; nepříbuzný dárce; mladiství; myelodysplastické syndromy; Treatment Outcome; homologní transplantace; antilymfocytární sérum; Transplantation Conditioning; lidé; ženské pohlaví; Humans; cyklofosfamid; Antilymphocyte Serum; Unrelated Donors; Female; lidé středního věku; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Middle Aged